Scanning tunneling microscopy study of CaF2 on Si(111): observation of metastable reconstructions. (23rd November 2021) - Galbiati, Miriam; Scarselli, Manuela; Arciprete, Fabrizio; De Crescenzi, Maurizio; Camilli, Luca
Abstract: The deposition of calcium fluoride (CaF2 ) on Si(111) at temperatures above 570 °C has been studied with scanning tunneling microscopy. At such temperatures, triangular calcium fluoride islands are formed both on terraces and along the phase domain boundaries of the (7 × 7) reconstruction of the Si(111) substrate. In addition to the formation of islands, we observe that CaF2 molecules react with the substrate inducing large areas of its surface to reconstruct into (√3 × √3) and c(2 × 4) phases. Upon annealing at 600 °C, the abovementioned areas of (√3 × √3) and c(2 × 4) turn into the stable (3 × 1) phase upon desorption of fluorine. Calcium fluoride islands are stable at this temperature. Depositions of calcium fluoride performed with Si substrate kept at higher temperature, namely at 680 °C, lead directly to the formation of (3 × 1) phase due to the complete desorption of fluorine, without passing through the formation of the metastable (√3 × √3) and c(2 × 4) phases. If CaF2 /Si(111) is brought at even higher temperatures, Ca also starts desorbing and the (7 × 7)-Si(111) reconstruction can eventually be restored.